Treatment of gastrointestinal stromal tumor (GIST) during bariatric surgery - Barros,Fernando de (2015)
The gastrointestinal stromal tumor (GIST) is a rare mesenchymal tumor. One should pay special attention when the GIST comes in obese patients during surgery. The laparoscopic resections with standard techniques, such as gastric bypass, have been described with good results. However, GIST resection associated sleeve gastrectomy for the treatment of obesity is rare, but can be done safely, depending on the location of the tumor.